THE IMPACT OF TRAINING, EMPLOYEE LOYALTY AND ORGANIZATIONAL CULTURE ON THE WORK ACHIEVEMENT : LITERATUR REVIEW - Ramdhani, Abel; Hadi, Syamsul; Purnamarini, Tri Ratna (International Conference on Humanity Education and Society (ICHES), 2024)
This paper aims to comprehend how training, employee loyalty, and organizational culture affect workers' achivment. An in-depth explanation of the elements that directly improve worker performance will be provided by this article. A systematic literature review (SLR) is used in this process. 30 papers were found through the use of the keywords "training, employee loyalty, organizational culture, and work performance" in a database that was obtained from Google Scholar publications. These articles were then assessed for this study. The application of articles discussing how training, employee loyalty, and organizational culture affect workers' achivment. This literature will show various types of different influences on work performance. The research results show that the resulting role of training, loyalty and organizational culture - from several literature reviews is proven to have a positive influence on work performance. This literature is also influenced by training, employee loyalty and organizational culture which is proven to have an influence on work performance. This is a finding in this research and can become a framework for empirical conceptual research